Natural History of Post-Treatment Kidney Stone Fragments: A Systematic Review and Meta-Analysis. Issue 3 (27th September 2021) - Brain, Eleanor; Geraghty, Robert M.; Lovegrove, Catherine E.; Yang, Bingyuan; Somani, Bhaskar K.
Abstract : Purpose: We assessed the literature around post-treatment asymptomatic residual stone fragments and performed a meta-analysis. The main outcomes were intervention rate and disease progression. Materials and Methods: We searched Ovid®, MEDLINE®, Embase™, the Cochrane Library and ClinicalTrials.gov using search terms: "asymptomatic", "nephrolithiasis", "ESWL", "PCNL", "URS" and "intervention." Inclusion criteria were all studies with residual renal fragments following treatment (shock wave lithotripsy, ureteroscopy or percutaneous nephrolithotomy). Analysis was performed using 'metafor' in R and bias determined using Newcastle–Ottawa scale. Results: From 273 articles, 18 papers (2, 096 patients) had details of intervention rate for residual fragments. Aggregate intervention rates for ≤4 mm fragments rose from 19% (20 months) to 22% (50 months), while >4 mm fragments rose from 22% to 47%. Aggregate disease progression rates for ≤4 mm rose from 25% to 47% and >4 mm rose from 26% to 88%. However, there was substantial difference in definition of "disease progression." Meta-analysis comparing >4 mm against ≤4 mm fragments: intervention rate for >4 mm (vs ≤4 mm): OR=1.50 (95% CI 0.70–2.30), p <0.001, I 2 =67.6%, tau 2 =0.48, Cochran's Q=11.4 (p=0.02) and Egger's regression: z=3.11, p=0.002. Disease progression rate for >4 mm: OR=0.06 (95% CI −0.98–1.10), p=0.91, I 2 =53.0%, tau 2 =0.57, Cochran's Q=7.11 (p=0.07) and Egger's regression: z=−0.75, p=0.45. Bias analysis demonstrated a moderate risk. Conclusions: Larger post-treatment residual fragments are significantly more likely to require further intervention especially in the long term. Smaller fragments, although less likely to require further intervention, still carry that risk. Notably, there is no significant difference in disease progression between fragment sizes. Patients with residual fragments should be appropriately counselled and informed decision-making regarding further management should be done.